Metal−Organic Framework-Based Ultrafast Logic Gates for High-Security Optical Encryption - Junhong Yu; Yadong Han; Longyu Wang; Yibing Liu; Hang Zhang; Xuan Chen; Xuezhi Liu; Zhengbang Wang; Jianbo Hu (Ultrafast Science, 2023)
Optical logic gates call for materials with giant optical nonlinearity to break the current performance bottleneck. Metal–organic frameworks (MOFs) provide an intriguing route to achieve superior optical nonlinearity benefitting from structural diversity and design flexibility. However, the potential of MOFs for optoelectronics has been largely overlooked and their applications in optical logic have not been exploited. Here, through temporally manipulating the nonlinear optical absorption process in porphyrin-based MOFs, we have successfully developed AND and XOR logic gates with an ultrafast speed approaching 1 THz and an on–off ratio above 90%. On this basis, all-optical information encryption is further demonstrated using transmittance as primary codes, which shows vast prospects in avoiding the disclosure of security information. To the best of our knowledge, this is the first exploration of MOFs for applications in ultrafast optical logic devices and information encryption.